2017
DOI: 10.14687/jhs.v14i3.4395
|View full text |Cite
|
Sign up to set email alerts
|

Examining to see elite sight-disabled athletes according to the dimensions of the scale of motivation in sport

Abstract: Made the purpose of this study is to examine to see disabled athletes according to the dimensions of the scale of motivation in sport. The study group is comprised of 168 visually impaired athletes in total, including 51 females and 117 males, identified by the targeted sampling method, between the ages of 15-25, who do sports at elite level. The Sport Motivation Scale (SMS) was developed by Pelletier (1995) basing on the Theory of Self Determination by Deci and Ryan (1985). The purpose of SMS is to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…With high motivation, an athlete would spend more time training and persist longer when facing adversity. Research indicates that disabled athletes have diverse motives to participate in competitive sports ( Mumcu et al, 2017 ). Also, some researchers found participating in competitive sports provided a means of affirming competence, promoting fitness, and delaying disabilities ( Page, O’Connor & Petersen, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…With high motivation, an athlete would spend more time training and persist longer when facing adversity. Research indicates that disabled athletes have diverse motives to participate in competitive sports ( Mumcu et al, 2017 ). Also, some researchers found participating in competitive sports provided a means of affirming competence, promoting fitness, and delaying disabilities ( Page, O’Connor & Petersen, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…They associate the psychological deficiencies of the athletes with the low motivation capacities or if any, problems or illnesses they can assert. The athletes with strong motivation level have high psychological levels (Mumcu, Acet, Kusan, Zambak, Koc 2017). People who are psychologically strong can continue their lives more easily and adapt to the current situation despite the risk factors caused by the traumatic lives (Guloglu and Karairmak, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It was previously demonstrated that there is a difference in the scores among the subscales of the athletes and the non-athletes [52][53][54]. The findings were strengthened by a few further studies, which described that the visually impaired athletes and the non-athletes had a significant difference in the psychological factors, which included socialization [55], well-being [56,57], and motivation [58].…”
Section: Discussionmentioning
confidence: 94%